Multiple cracking in deformed laminated metal-graphene composites. (1st May 2018) - Sheinerman, A.G.; Gutkin, M.Yu.
Abstract: A model is proposed for multiple cracking of graphene platelets in deformed laminated metal-graphene composites. Within the model, the first crack formed in a graphene platelet in the stress field of an applied load and a dislocation pileup emits dislocations that are accumulated near neighboring graphene platelets and lead to their cracking. Next, the process of dislocation emission from the existing cracks, their accumulation near neighboring graphene platelets and the cracking of these platelets repeats, eventually leading to multiple cracking of graphene platelets. We calculated the critical stress for the onset of cracking as a function of the structural parameters of the composites. The effect of amorphous layers around graphene platelets on fracture of metal-graphene composites is also briefly discussed.